Persistently high prevalence of HPV16 and rising prevalence of non-16/18 HR-HPV genotypes in cervical precancer and cancer in Latvia in 2016-2024 shape the severity of cervical disease - Sokolovska, Liba; Biserova, Karina; Spridzane, Arta; Krisane, Daira; Dudorova, Alesja; Gebrila, Svetlana; Krasovska, Ilvija; Perminov, Dmitry; Orlova, Beatrise; Petrovska, Marta; Jansons, Juris; Mitildzans, Androniks; et al. (Frontiers in Oncology, 2026)
BackgroundCervical cancer incidence and mortality in Latvia is one of the highest in Europe, but data on HR-HPV prevalence in cervical disease are lacking. We aimed to investigate HR-HPV prevalence in cervical squamous cell carcinoma (CSCC) and cervical dysplasia (CD), association with disease severity, and prevalence changes over time.Materials & MethodsCervical tissue samples from 145 patients were retrieved and used for HR-HPV genotyping using two commercially available PCR kits.ResultsOnly six CD samples were HR-HPV negative (6/66, 9.1%), while all CSCC were positive. Over 50% samples (75/139) harbored one, 33.8% two, 10.1% three, and 2.2% four HR-HPV genotypes. CSCC was more likely to harbor multiple HR-HPVs (p=0.0280). HPV16 remained most prevalent in CSCC and CD and was followed by HPV33 (32/139, 23.0%), HPV39 (13/139, 9.4%), and HPV18 (11/139, 7.9%). CSCC samples were more likely to have high HR-HPV loads (p=0.025). Disease severity expressed as CINI to CSCC grade 3, correlated with HR-HPVs detected (p=0.015, r=0.202) and HPV16 and HPV39 loads (p<0.001, r=0.354; p<0.001, r=0.307). prevalence decreased, insignificantly across the analyzed period, while HPV18 decreased significantly (2016-18: 17.4% vs. 2022-24: 2.2%; p=0.032). HPV66, 45, 39, 31, and 33 (2016-18: 13%; 2022-24:31.1%; p=0.045) increased.DiscussionHPV16 remained the most prevalent HR-HPV, while HPV18 decreased. Other HR-HPV genotypes (HPV 66/45/39/31/33) demonstrated an increase in prevalence. Cervical disease severity was linked to specific HR-HPV loads and the number infecting HR-HPVs. These findings highlight the need for extended HR-HPV genotyping with determination of viral load, and request more epidemiological studies analyzing historical and current samples.